Structural Glazing: Design under High Windload - P. Descamps (Challenging Glass Conference, 2016)
Bonding of glass onto aluminum frames, known as “Structural Silicone Glazing”, has been applied for more than 40 years in glass curtain wall facades. Silicone sealants are being used in this application because of their outstanding resistance to weathering (UV, temperature, moisture, ozone), They also provide resistance to water egress and thermal insulation. Their role, structurally, is to resist to windloads and to compensate for differential thermal expansion of glass and aluminum frame. For windload resistance, silicone bite is calculated using a simplified equation which assumes a uniform stress distribution along the sealant bite. Finite Element Analysis (FEA) was used in this study calculate the stress distribution in the sealant as a function of sealant bite and thickness and show the importance of the sealant geometry (bite and thickness) on the local stress distribution. The study shows that for glass deflections in the 1% region (L/d=100), large sealant joints and/or high modulus sealants lead to higher local stresses.